The Effect of Heating Rate on the Microstructure of a Soft-Annealed Medium Carbon Steel - Castro-Cerda, F (Wiley-VCH Verlag, 2017)
A comparative study on the microstructural changes after conventional (20 °C s−1) and ultrafast (300 °C s−1) heating is performed on a medium carbon steel in the soft annealed condition. Continuous-heating dilatometry experiments are carried out. The phase transformations and the volume phase fraction of austenite are determined among other microstructural changes. The microstructure is first observed using Optical Microscopy (OM), further characterized by Scanning (SEM), and detailed analyzed by Transmission Electron Microscopy (TEM). The effect of heating rate on the kinetics of cementite dissolution and austenite formation is rationalized. The experimental results are compared with Dictra calculations, and the possible effects on the kinetics of diffusion-controlled austenite formation are rationalized as well. Metallographic observations indirectly suggest the enhanced nucleation of austenite above Am. © 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim